Detection of Escherichia coli, Pseudomonas aeruginosa, Salmonella paratyphoid B, and Shigella dysentery in live Bacillus licheniformis products using propidium monoazide-real-time-quantitative polymerase chain reaction - Zheng, Xiaoling; Wang, Yinhuan; Gong, WanZi; Cai, Qianru; Li, Jue; Wu, Jiequn (Frontiers in Microbiology, 2022)
To eliminate the influences of excipients and interference of dead bacterial DNA on the detection of Escherichia coli, Pseudomonas aeruginosa, Salmonella paratyphoid B, and Shigella dysentery in live Bacillus licheniformis capsules, a polymerase chain reaction (PCR) method with high sensitivity and specificity was established. By combining bromide with propidium monoazide (PMA) -real-time quantitative PCR (qPCR) with microporous membrane filtration, excipients were removed, the filtrate was collected, and the bacteria were enriched using the centrifugal method. The optimal PMA working concentration, dark incubation time, and exposure time were determined. Specific E. coli, P. aeruginosa, S. paratyphoid B, and S. dysentery primers were selected to design different probes and a multiplex qPCR reaction system was established. The PMA-qPCR method was verified using different concentrations of dead and live bacteria. This method is efficient and accurate and can be widely applied to the detection of aforementioned pathogenic bacterial strains in live Bacillus licheniformis products.